Application of SMES unit to improve DFIG power dispatch and dynamic performance during intermittent misfire and fire-through faults - Yunus, A.M. Shiddiq; Abu-Siada, Ahmed; Masoum, Mohammad (IEEE, 2013)
The number of wind turbines connected to power grids has significantly increased during the last decade. This is mainly due to the convincing revolution in power electronic technology and the growing concern about greenhouse effect that is intensified due to the burning of fossil fuels. Variable speed wind energy conversion systems (WECS) such as doubly fed induction generators (DFIG) are dominating the wind energy market due to their superior advantages over fixed speed-based WECS that include more captured energy, less mechanical stress and acoustical noise. DFIG is interfaced to the ac network through grid side voltage source converter (GSC) and rotor side voltage source converter (RSC) to enable the variable speed operation of the wind turbine and to provide reactive power support to the ac grid during disturbance events. Converter switching malfunction such as misfire and fire-through may influence the power dispatch capability of the DFIG. In this paper, a super conducting magnetic energy storage (SMES) unit is utilized to improve the power dispatch and dynamic performance of DFIG-based WECS during internal converter switching malfunctions such as misfire and fire-through faults. Simulation results without and with SMES connected to the system are presented, compared and analyzed.